PERANCANGAN SISTEM MONITORING KOLAM IKAN MENGGUNAKAN GLOBAL SYSTEM FOR MOBILE COMMUNICATION BERBASIS ARDUINO UNO - Fazarullah, Muhamad; Hidayat, Rahmat; latifa, Ulinnuha (Politeknik Harapan Bersama Tegal, 2024)
The parameters of a pond water are very important to consider in cultivating a fish. Fish have many types of characteristics on pond water conditions and the level of turbidity of a pond. With the aim of this study designing a system device with monitoring that will measure the quality of acidity and turbidity water in a remote fish pond based on Arduino Uno. Monitoring is carried out using a GSM module which will provide message information in the form of statistical data on water quality measurements. The results of this study that the average turbidity level of fish reaches a maximum of 50 NTU and the acidity level in the water reaches a normal pH of 7.